Hubungan Antara Pola Asuh Dengan Status Gizi Pada Bayi - Aswin; Saryono; Ramawati, Dian (Jurnal Keperawatan Soedirman, 2008)
The childbearing pattern of babyÃ¢â‚¬â„¢s mother towards to a baby is really important to the development and growth of baby it self : however there are still many mothers who provide childbearing pattern, namely the exclusive breast milk thatÃ¢â‚¬â„¢s less complete six months, giving stimulant food of the breast milk before six months and many babies still do not have their complete immunization accordance with their age. The objective of this research is to know the relationship between the childbearing pattern and the state of the babyÃ¢â‚¬â„¢s nutrition.The research carried out in the Village of Wangon, Wangon District, Banyumas Regency in the year of 2007. The type of research is analytic with the approach of cross sectional study. The respondents amount to forty mothers at the twelve integrated health services center in the village of Wangon with inclusive criteria having babyÃ¢â‚¬â„¢s in the age of six months up to twelve months. The data analysis used was the Fisher's exact test.The result of the research indicated that the sum of 70 percent of the babies got exclusive breast feeding, completed food of breast feeding accordance with their age. Based on the fisher exact research, it was gotten the score P = 0,021 < alpha (a = 0,05 ) that indicated that there was the relationship between the childbearing pattern and the nutrition status of the babies. The conclusion of the research is that the good childbearing pattern willÃ‚Â  improve the babyÃ¢â‚¬â„¢s nutritionÃ‚Â  status.Ã‚Â Ã‚Â